The Miners of South America: Impacts of Climate Change on the Distribution of Geositta Miners Along Elevational Gradients - Meireles, Ricardo C.; Lopes, Leonardo E.; Brito, Gustavo R. [UNESP]; Solar, Ricardo (Wiley, 2025)
ABSTRACT Range shifts along elevational gradients are a common response of species to changing climate, particularly in tropical regions where temperature decreases sharply with elevation. In this study, we investigate the current and future distribution of seven Geositta species (Furnariidae), which inhabit arid and semi‐arid open habitats across different elevations in South America. Using ecological niche modeling, we assessed climatic suitability under two climate change scenarios: an optimistic scenario with reduced emissions and a pessimistic scenario with continued high emissions. Species distribution models were generated with the MAXENT algorithm, using 100 replicates per species. Future projections, based on two General Circulation Models (2061–2080), evaluated the influence of elevation on climatic niche availability. Our results indicate that six of the seven Geositta species will likely face significant habitat loss under all scenarios, with the pessimistic scenario causing the most severe reductions. Climatic suitability patterns differed between lowland and highland species, influenced by vegetational and elevational zonation of the Andean slopes. For highland species, suitable conditions were mostly restricted to higher elevations within their current ranges, reflecting the geographic constraints that limit their ability to shift upslope. These findings highlight the vulnerability of Geositta to climate change, stressing the urgency of conservation efforts. Protecting mid‐ to high‐elevation habitats and transitional zones, while reducing anthropogenic pressures, will be key to safeguarding species with limited dispersal abilities. Although our models suggest most species are likely to retain substantial portions of their climatically suitable range, their future persistence may still depend on habitat availability, dispersal capacity, and other ecological constraints. RESUMO Mudanças na distribuição ao longo de gradientes altitudinais são uma resposta comum das espécies às alterações climáticas, especialmente em regiões tropicais, onde a temperatura diminui rapidamente com a elevação. Investigamos a distribuição atual e futura de sete espécies de Geositta (Furnariidae), que ocupam habitats abertos áridos e semiáridos em diferentes altitudes na América do Sul. Utilizando modelagem de nicho ecológico, avaliamos a adequação climática sob dois cenários: otimista, com redução das emissões de gases de efeito estufa, e pessimista, com emissões contínuas elevadas. Os modelos de distribuição foram gerados com o algoritmo MAXENT, utilizando 100 réplicas por espécie, e projeções futuras baseadas em dois Modelos de Circulação Geral (2061–2080) permitiram avaliar o efeito da altitude na disponibilidade do nicho climático. Seis das sete espécies provavelmente sofrerão perdas significativas de habitat em todos os cenários, sendo o pessimista o mais severo. Padrões de adequação climática diferiram entre espécies de baixada e de altitude, influenciados pela zonação vegetacional e altitudinal das encostas andinas. Para as espécies de altitude, as condições adequadas restringiam‐se principalmente a altitudes mais elevadas dentro de suas áreas de distribuição atuais, refletindo as limitações geográficas que restringem sua capacidade de migrar para altitudes mais elevadas. A proteção de habitats de elevação média e alta e de zonas de transição, junto à redução de pressões antrópicas, será crucial para a conservação de espécies com dispersão limitada. Embora a maioria das espécies deva manter áreas climaticamente adequadas, sua persistência futura dependerá da disponibilidade de habitat, capacidade de dispersão e outras restrições ecológicas.